Juvenile Systemic Sclerosis Presenting With Severe Pulmonary Vascular Disease: ECMO Stabilization During Aggressive Therapy Resulting in a Favorable Outcome - Stephanie M. Tsoi; Shannon Cheung; Roberto Alejandro Valdovinos; Elena Amin; Hythem Nawaytou; Elizabeth Colglazier; Claire Parker; April Edwell; Susan Kim; Jeffrey R. Fineman (Pulmonary Circulation, 2025)
ABSTRACT Juvenile systemic sclerosis (jSSc) associated pulmonary hypertension (PH) is rare, but, the leading cause of morbidity and mortality in jSSc. This is a case of a 10‐year‐old girl whose initial presentation of positive U3‐RNP antibody jSSc included diffuse skin findings, severe pulmonary arterial hypertension, and right ventricular failure. Veno‐arterial extracorporeal membranous oxygenation (VA‐ECMO) and atrial stent placement facilitated treatment with pulse‐dose steroids, mycophenolate mofetil, and B‐cell depleting therapy to treat the underlying autoimmune inflammation and triple therapy with treprostinil, ambrisentan, and tadalafil for her pulmonary hypertension. At 9‐month follow‐up, her jSSc is well‐controlled with complete resolution of her PH. This case demonstrates that multi‐disciplinary treatment, including upfront multi‐drug therapy for jSSC and PAH, that included VA‐ECMO, may improve outcomes, particularly when treatment for underlying causes (in this case, jSSc) is just being initiated.